PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PT. WISLEY GOLF & SPORT CENTRE - SUHENDRY TAN; PUTU . (LP2MTBM MAKARIOZ, 2020)
In general, every agency/company have a target to archive which is to gain rapid improvement and able to survive in thisbusiness world. But, every company often have a issue or problem on implementing their strategy which will cause anagency/company to fail to archive their target, due to that, researcher aim to find and research the problem that occur in theagency/company to be able to provide a result and solution for them. One of the issue that often occur in anagency/company is customer satisfaction. PT Wisley Golf & Sport Centre have a few issue on increasing the customersatisfaction which is facility and service quality. This research is a quantitative research which using questionnaire as amethod to collecting data. Sampling in this research are using saturated sampling technique with the total of 127 people.Data analysis used in this research are descriptive analysis, data quality test, classical assumption test, influence andhypothesis test using the software programe SPSS version 25. The results in this research shown that judging from the Ttest result, researcher found that facility have a partially significant impact on customer satisfaction and also service qualityhave a partially significant impact on customer satisfaction. Result on F test has shown that the facility and service qualitytogether have an significant impact on customer satisfaction.